Pengaruh Iklim Komunikasi terhadap Identifikasi Organisasi melalui Budaya Emosional Karyawan di Perguruan Tinggi Bandung - Iskandar, Muhammad Hanif Fatahillah; Sugiana, Dadang; Aristi, Nindi (JURNAL LENSA MUTIARA KOMUNIKASI, 2024)
This study examines the influence of communication climate on organizational identification among university employees in Bandung, mediated by emotional culture. The research is based on Gibb's (1961) communication climate theory, organizational identification by He and Brown (2013), and emotional culture by Yue (2020). The method used is multiple regression analysis with the help of SPSS 21 software, involving 178 respondents. The results indicate that a supportive communication climate contributes 33.3% to organizational identification, while a defensive communication climate contributes 18.7%. Additionally, the communication climate significantly influences emotional culture with a contribution of 77.8%, and emotional culture affects organizational identification with a contribution of 35.1%. Overall, the communication climate significantly impacts organizational identification through emotional culture with a contribution of 43.6%.